WAKTU DENGUNG EFEKTIF UNTUK DESAIN MULTIFUNGSI AUDITORIUM PENDIDIKAN - DYAH NURWIDYANINGRUM; SRI KURNIASIH (Jurnal Poli-Teknologi, 2013)
ABSTRACT Auditorium is meeting closed space that designed for acoustical quality purposes. In education field, auditorium is needed as primary supporting education facilitation. University generally use auditorium for multifunction activities such as public lecture, art performance, research seminar and exibition. Reverberation timeis one of methodto measure acoustic quality in closed spaceespecially auditorium. For multifucntion auditorium, reverbaration time target range around 0,5 – 1 second. Existing reverberation time calculation become a reference in prequisites achievement that is targeted. Space planes surface redesign included floor, wall, plafond and interior influences prequisites achievement. Another, space planes surface redesign should improve aesthetic value and space fucntion supporting value.comparasion between existing and redesigned calculation shows that prequisites is achieved with change interior arrangement (chairs and tables), correct stage backgroud material, streamline coridor plafond shape, replace diffuser on main plafond, and repair unefective reflective wall Keywords : reverberation time, diffuser, acoustic